PEMBELAJARAN MENULIS TEKS BERITA BERFOKUS PADA STRUKTUR TEKS MENGGUNAKAN METODE NATURE LEARNING PADA PESERTA DIDIK KELAS VIII DI SMP ANGKASA LANUD HUSEIN SASTRANEGARA - Meisya Adinda; Eggie Nugraha; Musaddad Abdul Azis; Dheni Harmaen (STKIP Subang, 2023)
This study is motivated by the low ability of students in writing news texts. This is because educators are less creative in choosing learning methods and less motivating students to write. The formulation of the problem compiled by the author is the author's ability to plan, implement, apply the ability to write news texts focusing on text structure using the nature learning method, the ability before and after using the nature learning method, and the difference in the ability of students to write news texts after using the nature learning method. The objectives of this study include to test the author in planning, implementing, applying, and evaluating the nature learning method in writing news texts, testing the ability of students before and after using the nature learning method, and testing the difference in the ability to write news texts using the nature learning method. The method used is quantitative method. The object of this research is students of class VIII of SMP Angkasa Lanud Husein Sastranegara Bandung, using two classes as experimental and control classes. The results showed that the ability to write news texts of grade VIII students at SMP Angkasa Lanud Husein Sastranegara Bandung was in the good category. This is supported by the data of the average results of the pretest of 40.00 and posttest of 84.80. Thus, the nature learning method is effectively used to improve the ability to write news texts. In addition, the nature learning method is significant in improving the ability to write news texts, this is proven based on the results of statistical calculations using the Mann Whitney-U Test which shows that the Asymp. Sig. 0,021<0,05. Based on the results of the study, the nature learning method is effective and can be used as an alternative in learning to write news texts in class VIII.